A single-particle trigger for time-of-flight measurements in prompt-gamma imaging - Magalhães Martins, Paulo; Dal Bello, Riccardo; Seimetz, Michael; Hermann, German; Kihm, Thomas; Seco, Joao (Frontiers in physics, 2020)
Tracking of single particles accelerated by synchrotrons is a subject that crosses several physics fields. The high clinical intensities used in particle therapy that can exceed 10(9)p/s make this task very challenging. The tracking of the arrival time of single particles in the ion beam is fundamental for the verification of the particle range and dose delivered to the patient. We present a prototype made of scintillating fibers which has been used to provide time-of-flight (TOF) information for three beam species currently accelerated at the Heidelberg Ion-Beam Therapy Center (HIT). We have demonstrated a time-tracker for a prompt-gamma spectroscopy system that allows for a background TOF rejection with a sub-nanosecond time resolution.
Gesehen am 01.06.2021